COMMD7 as a novel NEMO interacting protein involved in the termination of NF‐κB signaling. Issue 1 (28th September 2015) - Esposito, Elio; Napolitano, Gennaro; Pescatore, Alessandra; Calculli, Giuseppe; Incoronato, Maria Rosaria; Leonardi, Antonio; Ursini, Matilde Valeria
Abstract : NEMO/IKKγ is the regulatory subunit of the IκB Kinase (IKK) complex, required for the activation of the NF‐κB pathway, which is involved in a variety of key processes, including immunity, inflammation, differentiation, and cell survival. Termination of NF‐κB activity on specific ‐κB responsive genes, which is crucial for the resolution of inflammatory responses, can be achieved by direct degradation of the chromatin‐bound NF‐κB subunit RelA/p65, a process mediated by a protein complex that contains Copper Metabolism Murr1 Domain 1 (COMMD1). In this study, we identify COMMD7, another member of the COMMDs protein family, as a novel NEMO‐interacting protein. We show that COMMD7 exerts an inhibitory effect on NF‐κB activation upon TNFα stimulation. COMMD7 interacts with COMMD1 and together they cooperate to down‐regulate NF‐κB activity. Accordingly, termination of TNFα‐induced NF‐κB activity on the ‐κB responsive gene, Icam1, is defective in cells silenced for COMMD7 expression. Furthermore, this impairment is not greatly increased when we silence the expression of both COMMD7 and COMMD1 indicating that the two proteins participate in the same pathway of termination of TNFα‐induced NF‐κB activity. Importantly, we have demonstrated that COMMD7's binding to NEMO does not interfere with the binding to the IKKs, and that the disruption of the IKK complex through the use of the NBP competitor impairs the termination of NF‐κB activity. We propose that an intact IKK complex is required for the termination of NF‐κB‐dependent transcription and that COMMD7 acts as a scaffold in the IKK‐mediated NF‐κB termination. J. Cell. Physiol. 230: 152–161, 2016. © 2015 Wiley Periodicals, Inc.